2021
DOI: 10.3389/fbioe.2021.660502
|View full text |Cite
|
Sign up to set email alerts
|

3D Cancer Models: The Need for a Complex Stroma, Compartmentalization and Stiffness

Abstract: The use of tissue-engineered 3D models of cancer has grown in popularity with recent advances in the field of cancer research. 3D models are inherently more biomimetic compared to 2D cell monolayers cultured on tissue-culture plastic. Nevertheless 3D models still lack the cellular and matrix complexity of native tissues. This review explores different 3D models currently used, outlining their benefits and limitations. Specifically, this review focuses on stiffness and collagen density, compartmentalization, tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 64 publications
(70 reference statements)
1
77
0
Order By: Relevance
“…As a result, there is growing interest in the development and use of 3D cancer in vitro models for the replacement of 2D in vitro models and reduction in the use of animal models, the latter of which is an important objective in terms of the 3R framework (replace, reduction, and refinement of animals) [ 41 , 42 ]. 3D models for pre-clinical treatment testing are emerging to more realistically recapitulate TMEs, and more specifically TME hallmarks that are associated with treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there is growing interest in the development and use of 3D cancer in vitro models for the replacement of 2D in vitro models and reduction in the use of animal models, the latter of which is an important objective in terms of the 3R framework (replace, reduction, and refinement of animals) [ 41 , 42 ]. 3D models for pre-clinical treatment testing are emerging to more realistically recapitulate TMEs, and more specifically TME hallmarks that are associated with treatment resistance.…”
Section: Introductionmentioning
confidence: 99%
“…PEG has been used for various 3D culturing and tissue engineering applications. For example, PEG has been cultured with breast cancer cells and CAFs to evaluate drug resistance through pathways associated with tumour-stromal interactions (107,108). In another study, Caiazzo et al found that PEG can facilitate pluripotency by manipulating the microenvironment of the matrix to create a "reprogramming niche" that promotes MET and increased epigenetic remodeling capable of shifting the somatic cell fate (109).…”
Section: Hydrogel Scaffold Modelsmentioning
confidence: 99%
“…Their main advantages are their low cost, ease of use, reproducibility and suitability for high-throughput assays [ 135 ]. However, when using MCTs, future improvements include an increased resemblance to solid tumors and their microenvironment, for example, the tumor vasculature, components of the immune system, mechanical signals and fluid dynamics [ 9 , 135 , 140 ]. It is crucial to overcome the difficulty to acquire high-resolution images of drug penetration and cell invasion through spheroids because of the loss of image quality, poor light scattering and lack of compartmentalization between cancer and stromal cells [ 9 , 130 , 134 , 140 ].…”
Section: 3d Ovarian Cancer Modelsmentioning
confidence: 99%
“…In particular, we focus on self-assembly strategies that have been engineered to overcome the challenges presented by animal models and current 3D in vitro models. Readers are referred to the following reviews for complementary information [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%